A review of pharyngeal mucosal closure technique in total laryngectomy - Govindasamy, Gopu; Shanmugam, Subbiah; Murugan, Arul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: The purpose of this retrospective analysis was to review our single institute based experience with the pharyngocutaneous fistula following total laryngectomy and to determine the impact of pharyngeal closure technique in the development of PCF in our patients. Methods: The medical records of the patients, who underwent total laryngectomy for squamous cell carcinoma of the larynx and hypopharynx in Government Royapettah Hospital, center for oncology between January 2010 and December 2017, were retrospectively reviewed. Results: 26 patients were included in the study of which 25 were male and 1 was female. Mean age of the patients were 58 years. Horizontal closure was done in 9 patients (35%) and T closure was done in 17 patients (65%). PCF was observed in 1 of 9 patients in horizontal closure. Remaining 17 patients underwent T closure of whom 8 patients developed PCF (p=0.06). Eight out of 18 patients (44%) developed PCF after salvage surgery after radiotherapy failure, Remaining 8 patients underwent primary laryngectomy for advanced stage cancers with cartilage involvement, of whom 1 patient developed PCF (12.5%) (p=0.11). In salvage laryngectomy (n=18), 1 of 6 cases developed PCF in horizontal closure and 7 of 12 cases in T closure technique (p=0.09). Conclusions: The incidence of fistula in our study was 34%. Horizontal closure was associated with decreased incidence of PCF when compared to ‘T’ closure of the defect. Prior radiotherapy had increased incidence of PCF.